Manajemen Konflik Bernuansa Islami di SD Ramah Anak Kota Lhokseumawe - Jamaluddin Idris; Herawati Herawati (Institut Agama Islam Negeri Palopo, 2019)
In order to maintain the stability of the quality of Islamic education; Islamic conflict management in Child Friendly Elementry School (CFES) is a necessity; in order to minimize the chance of conflict and bring friendliness evenly to all HR in schools, including teachers; as one of the most critical components in the education process in elementary school. The purpose of this study is to find out; (1) the forms of conflict that occurred, (2) technical and (3) Islamic nuance conflict regulation strategies applied at the Lhokseumawe CFES, and (4) CFES efforts to minimise conflict. This study uses a qualitative approach using techniques: documentation review, direct observation, and in-depth interviews conducted with principals and teachers, to obtain data and information related to the four objectives of this study. The results of the study show that: six forms of conflict occur in CFES, namely conflict: within individuals, between individuals, between individuals and groups/divisions, between groups/groups, between organisations, and between individuals in different organisations. Domination of conflict only occurs in the personal aspects of the teacher, which is motivated by family reasons, limited capacity, heavy workload, etc. However, every conflict that emerges can be implemented well, based on three technical management of conflict, namely: identification of conflicts, evaluation of conflict and resolution of conflicts that are Islamic in nature through a spiritual/religious and family approach (ukhuwah). Islamic nuances of conflict management strategies applied in CFES very prioritising collaboration, accommodation, compromise (deliberation), communication, and negotiations that prioritise the values of ukhuwah Islamiyah. An added benefit of CFES in minimising conflict is to have three specific things, namely: having conflict prevention programs and policies, having a structured conflict management program, and having a climate/culture and teacher friendly social interaction; which is always applied in all aspects of the implementation of education in schools.Manajemen Konflik Bernuansa Islami Di Sd Ramah Anak Kota Lhokseumawe